Respostas
respondido por:
5
x + y = 43
4x + 2y = 150
multiplica a primeira equação por - 2
- 2x - 2y = - 86
4x + 2y = 150
soma as duas
2x = 64
x = 64 / 2
x = 32
x + y = 43
32 + y = 43
y = 43 - 32
y = 11
S = {32, 11}
4x + 2y = 150
multiplica a primeira equação por - 2
- 2x - 2y = - 86
4x + 2y = 150
soma as duas
2x = 64
x = 64 / 2
x = 32
x + y = 43
32 + y = 43
y = 43 - 32
y = 11
S = {32, 11}
rosielmoreiraosxn9i:
obrigado
respondido por:
1
Boa noite Rosiel
x + y = 43
2x + y = 75
2x - x = 75 - 43
x = 32
32 + y = 43
y = 43 - 32 = 11
x + y = 43
2x + y = 75
2x - x = 75 - 43
x = 32
32 + y = 43
y = 43 - 32 = 11
Perguntas similares
6 anos atrás
6 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás